1996
DOI: 10.1007/bf01845763
|View full text |Cite
|
Sign up to set email alerts
|

Dose-ranging evaluation of the antiemetic efficacy of intravenous dolasetron in patients receiving chemotherapy with doxorubicin or cyclophosphamide

Abstract: Selective 5-HT3 antagonists have proven to be safe and effective for the prevention of chemotherapy-induced nausea and vomiting. Dolasetron is a new highly selective addition to this class of antiemetics that has been shown to have significant antiemetic activity in patients receiving cisplatin-containing regimens. This pilot study was designed to evaluate the antiemetic efficacy of dolasetron in cancer patients receiving doxorubicin and/or cyclophosphamide. This study used an open-label, non-randomized design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…As in previous dolasetron studies [14,15,23,30,31] and other 5-HT 3 antagonists trials [32,33], tiredness and headache were the most commonly reported adverse events. As in previous studies with 5-HT 3 receptor antagonists [3,13,15,22,23,31,32,34], we also noted asymptomatic changes in ECG intervals. None was of clinical consequence or required medical treatment.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…As in previous dolasetron studies [14,15,23,30,31] and other 5-HT 3 antagonists trials [32,33], tiredness and headache were the most commonly reported adverse events. As in previous studies with 5-HT 3 receptor antagonists [3,13,15,22,23,31,32,34], we also noted asymptomatic changes in ECG intervals. None was of clinical consequence or required medical treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Patients in the 2.4-mg/kg group may have been more ill and therefore more difficult to manage. This could explain the poorer results in this dosage level compared to the 1.8-mg/kg group, although a decreased effect with 2.4 mg/kg has also been noted in adults [13,22,23]. As in adults, MDL 74,156, the reduced metabolite of dolasetron, appeared rapidly in the plasma of pediatric cancer patients.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Substantial evidence supports these conclusions, particularly with ondansetron, the first 5-HT 3 receptor antagonist developed. Early clinical trials of intravenous ondansetron with cisplatin explored a variety of schedule-related issues, including variable dosing intervals, number of doses, and schedules incorporating continuous infusion [22,50]. In general, these studies demonstrated that shortening the dosing interval or increasing the number of doses did not improve efficacy.…”
Section: Schedule Of Administration Of 5-ht 3 Antagonist Antiemeticsmentioning
confidence: 99%